Pengaruh Promosi penjualan dan E-Service Quality terhadap Minat Beli Ulang Melalui Kepuasan Pelanggan (Studi pada pelanggan Gopay di Jabodetabek) - Dinar Rian Fiona; Wahyu Hidayat (Universitas Diponegoro, 2020)
The growth of cashless society in Indonesia has undergone significant transformation in the past 3 years. It makes Gopay as pioneer in Indonesian digital wallet have to compete with the competitors to gain customer’s repurchase intention. This paper studies the impact of sales promotion and e-service quality on customer’s intention of repurchasing through customer satisfaction in the setting of digital wallet Gopay. The sample of this research is 100 respondents who have been using Gopay before. This primary data collected with questionnaire and observation. Data analyse with linear regression. All respondents are collected using purposive sample technique. The result of the research indicate that sales promotion and e-service quality has significant effect on customer satisfaction. Sales promotion and e-service quality also has significant effect on repurchase intention